THE EFFICIENCY OF USING SEXED SEEDS IN ARTIFICIAL INSEMINATION OF CATTLE (ResearchJet Journal of Analysis and Inventions, 2023)
In this article, the efficiency of obtaining female calves by insemination with female seeds of the Black-Ola cattle breed cows, which are kept on a large scale by the population of our country, is presented. The live weight of cows bred with same-sex seeds, the characteristics of seed retention, and growth indicators were studied.